1 ) \(x^2+x+1=x^2+x+\dfrac{1}{4}+\dfrac{3}{4}=\left(x+\dfrac{1}{2}\right)^2+\dfrac{3}{4}\ge\dfrac{3}{4}>0\forall x\left(đpcm\right)\)
2 ) \(x^2+3x+3=x^2+3x+\dfrac{9}{4}+\dfrac{3}{4}=\left(x+\dfrac{3}{2}\right)^2+\dfrac{3}{4}\ge\dfrac{3}{4}>0\forall x\left(đpcm\right)\)
3 ) \(x^2+y^2+2\left(x-2y\right)+6\)
\(=x^2+y^2+2x-4y+6\)
\(=\left(x^2+2x+1\right)+\left(y^2-4y+4\right)+1\)
\(=\left(x+1\right)^2+\left(y-2\right)^2+1\ge1>0\forall x\left(đpcm\right)\)
1) x2 +x+1
= (x2 +2.x.1/2 +1/4) +3/4
= (x+1/2)2+3/4 \(\ge\dfrac{3}{4}\forall x\in R\left(Vì:\left(x+\dfrac{1}{2}\right)^2\ge0\forall x\in R\right)\)
2) x2 + 3x+3
= (x2 +2.x.3/2 + 9/4)+ 3/4
= ( x+ 3/2)2 + 3/4 \(\ge\dfrac{3}{4}\forall x\in R\left(Vì:\left(x+\dfrac{3}{2}\right)^2\ge0\forall x\in R\right)\)